2005
DOI: 10.1007/s11282-005-0035-2
|View full text |Cite
|
Sign up to set email alerts
|

Image-based diagnosis of condylar head fractures of the mandible: four case studies

Abstract: This paper reports the four cases of the condylar head fractures of the mandible. The diagnostic images with panoramic radiograph and CT are presented. From 4 cases of condylar head fractures, the incidence, causes, and mechanisms are also discussed together with previous report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The condylar region is often involved in mandibular and maxillofacial fractures that may result in severe changes of the TMJ, and furthermore, they can affect the functions of this joint (Fortunato et al ., ; Huelke et al ., ; Huelke & Patrick, ; Kawai et al ., ; Oji, ; Wang et al ., ). Of the mandibular fractures, the condylar type occurs most frequently because of the slenderness of the condylar neck.…”
Section: Introductionmentioning
confidence: 99%
“…The condylar region is often involved in mandibular and maxillofacial fractures that may result in severe changes of the TMJ, and furthermore, they can affect the functions of this joint (Fortunato et al ., ; Huelke et al ., ; Huelke & Patrick, ; Kawai et al ., ; Oji, ; Wang et al ., ). Of the mandibular fractures, the condylar type occurs most frequently because of the slenderness of the condylar neck.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, panoramic radiographs have demonstrated that bone density in the dental and molar regions of the human mandible is higher in males than in females 11−12, 30, 32, 36−38) . Therefore, the structure of cortical bone is one of the most important factors contributing to mandibular fracture 20) . Despite these findings regarding other regions of the mandible, the thickness of the cortical bone in the head and neck of the mandible has not been determined using cone-beam computed tomography (CBCT).…”
mentioning
confidence: 99%